EVALUATION OF ANTIOXIDANT ACTIVITY OF DIFFERENT EXTRACTS OF MEDICINAL PLANTS - S, KARTHIKA; N, KANNAPPAN; TNK, SURIYAPRAKASH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present study was carried out to evaluate the antioxidant activity of different extracts of two medicinal plants. Methods: In-vitro antioxidant activity of different extracts of Hydrocotyle javanica Thunb and Peristrophe bicalyculata (Retz.) Nees were determined by following methods such as Lipid peroxide assay (LPO), nitric oxide assay (NO), glutathione (GSH), catalase (CAT). Results: Among eight different extracts, n-Hexane H. javanica extract and alcoholic P. bicalyculata extract showed more potent in vitro antioxidant activity in terms of LPO, NO, GSH, SOD, and CAT assay. Conclusion: From the results, it can be concluded that n-Hexane H. javanica extract and alcoholic P. bicalyculata extract showed more potent in vitro antioxidant activity.